Psychosocial problems experienced by substance addicts, implemented evidencebased interventions and the role of nursing - Cüceler, Seval; Yılmaz, Mualla; Türkleş, Serpil (Journal of Dependence, 2022)
Substance addiction is an important public health problem that negatively affects the health of the individual, family life, the safety of the society and the economy. A multidisciplinary approach is required in the fight against substance addiction. Substance addiction causes many psychosocial problems such as education, economy, social relations and stigma, emotional and psychiatric problems.In this review, the psychosocial dimensions of substance addiction, the role of the nurse in the psychosocial care of the individual and the family, what should be done with the evidence-based nursing interventions are explained in all dimensions, and it is aimed to draw attention to the subject by presenting examples of evidence-based intervention studies conducted by other disciplines for the substance addicted individual and his family.
Keywords: Substance dependence; psychosocial factors; nursing; evidence-based nursing